Fate of Pathogen Indicators During Extended Aeration Wastewater Treatment - Mohamed Sunar, Norshuhaila; Maslan, Masayu; Kamaruddin, Saidatu Salwa (International Journal of Integrated Engineering, 2015)
Pathogen indicators normally used in water quality indicator because large numbers of the bacteria are always present in the faeces of humans, but are not naturally found in water. Since these bacteria don’t live long in water once outside the intestine, their presence in water means there has been recent contamination through effluent discharges or other sources. Like other enteric pathogens, a common mode of transmission for E.coli is via contaminated water, food and by direct person to person contact. Infection often causes severe bloody diarrhea, abdominal cramps, and possibly fever. In some cases, infection can lead to kidney failure and possibly death. In order to evaluate the effieciency of extended aeration wastewater treatment plant (EAWWTP), the microbial analyses such as enumeration of E.coli and total coliform were measured. Besides, this study also involved the measurements of pH, turbidity, DO (Dissolve Oxygen), BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand) and TSS (Total Suspended Solid). This study summarized that each treatment process provides important roles to overall effieciency of EAWWTP. The secondary treatment was proved sufficient not only on reducing pathogen indicators but for all examined parameters. Significantly, this study conclude that numbers of pathogen indicators discharges in effluent meet the regulated standard guideline after treated through the EAWWTP.